Automatic optimization of centrifugal pump for energy conservation and efficiency enhancement based on response surface methodology and computational fluid dynamics - Wang, Chuan; Yao, Yulong; Yang, Yang; Chen, Xionghuan; Wang, Hui; Ge, Jie; Cao, Weidong; Zhang, Qiqi (Engineering applications of computational fluid mechanics, 2023)
Centrifugal pumps are widely used in various fields and have enormous energy-saving potential. In order to predict efficiency quickly and accurately, firstly, by establishing a hydraulic loss model for centrifugal pump impellers, the functional relationship between impeller hydraulic loss and hydraulic efficiency is constructed to establish the objective function. Secondly, calculate the main dimensions of the impeller using the velocity coefficient method and establish the objective function variables of the number of blades Z and outlet placement angle β 2 . And the velocity coefficient k 0 . Then, the method of mathematical statistics, namely response surface analysis, is used to solve the relationship between hydraulic efficiency and dependent variables within the range of variables, which plays the role of predicting hydraulic efficiency. Finally, the accuracy of the predictions is verified by numerical simulation. The results show that the hydraulic efficiency of a high specific speed centrifugal pump reaches its maximum at 1000m 3 /h operating conditions with a blade number of 3, a speed coefficient of 3.9 and an outlet angle of 30°. The study provides a new direction for the hydraulic design of high specific speed centrifugal pumps to achieve more accurate predictions of high specific speed centrifugal pump efficiency.